1996
DOI: 10.1210/endo.137.5.8612568
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast function is activated by osteoblastic cells through a mechanism involving cell-to-cell contact.

Abstract: We have established a method for obtaining an enriched preparation of functionally active osteoclast-like multinucleated cells (enriched OCLs) from co-cultures of mouse primary osteoblasts and bone marrow cells. Using these enriched OCLs, the effect of osteoblastic cells on osteoclast function was examined in two assays: a pit formation assay and an assay for actin ring formation. The enriched OCLs cultured for 24 h on dentine slices formed only a few resorption pits. When various numbers of primary osteoblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
113
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(115 citation statements)
references
References 0 publications
2
113
0
Order By: Relevance
“…Osteoblasts can support osteoclastogenesis by expressing RANKL molecules on their surface, (12)(13)(14) suggesting the importance of both RANKL expression levels at the whole-cell level and RANKL subcellular localization. While numerous studies have focused on RANKL transcriptional regulation, contributing to an understanding of the regulatory mechanisms of RANKL expression at the whole-cell level, (40)(41)(42) the subcellular localization of RANKL in osteoblastic cells has not been widely investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoblasts can support osteoclastogenesis by expressing RANKL molecules on their surface, (12)(13)(14) suggesting the importance of both RANKL expression levels at the whole-cell level and RANKL subcellular localization. While numerous studies have focused on RANKL transcriptional regulation, contributing to an understanding of the regulatory mechanisms of RANKL expression at the whole-cell level, (40)(41)(42) the subcellular localization of RANKL in osteoblastic cells has not been widely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…(9)(10)(11) However, only RANKL molecules expressed at the cell surface actually can bind to RANK, which is located at the cell surface of osteoclast precursor cells. (12)(13)(14) Therefore, the quantity of RANKL on the osteoblastic cell surface could determine the magnitude of the signal input and the degree of osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] M-CSF is essential for not only the proliferation of osteoclast progenitors, but also for differentiation into mature osteoclasts and survival in vitro. 27 In contrast, OPG was reported to inhibit osteclastogenesis competing with the binding of RANKL to the RANK.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane-bound proteins, receptor activator of nuclear factor κB ligand (RANKL), and soluble macrophage colony-stimulating factor (M-CSF) are considered essential factors for osteoclastogenesis produced by osteoblasts and bone marrow stromal cells. [3][4][5][6] In contrast, osteoprotegerin (OPG), a soluble tumor necrosis factor (TNF) receptor homolog, was found to inhibit osteclastogenesis by competing with the binding of RANKL to the RANK (receptor of RANKL). 7 …”
Section: Introductionmentioning
confidence: 99%
“…(6)(7)(8) Therefore, the amount of RANK ligand (RANKL) on the osteoblastic cell surface, where RANKL binds to RANK through cell-to-cell contact and triggers downstream signaling in osteoclast precursors, is considered to determine the magnitude of the signal input and the degree of osteoclastogenesis. (9,10) Previously, we have shown that most of the newly synthesized RANKL is transferred from the Golgi apparatus to the lysosomal storage compartment via the route involving vacuolar protein sorting 33a (Vps33a) in osteoblastic cells. (11) There also exists the minor pathway transporting RANKL from the Golgi apparatus to the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%